2023
DOI: 10.12912/27197050/154912
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and Economic Study of Wheat Winter Varieties by Different Geographical Origin

Abstract: The results of research on increasing resistance of winter wheat varieties of different geographical origins to adverse weather conditions in the zone of unstable moistening in the North-Eastern Forest Steppe of Ukraine have been summarized. Rational use of agrometeorological resources made it possible to determine optimal terms of work on the elements of cultivation technology, taking into account weather conditions of the current year nd on their basis, to improve adaptive technologies for growing winter whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…Szumiło and Rachoń [43] reported that delaying the sowing date primarily reduced the number of spikes per square meter. Sobko et al [44] demonstrated in their Jarecki and Czernicka [40] confirmed the usefulness of field measurements of plant parameters, such as SPAD and LAI, in assessing the effectiveness of fertilization of winter wheat and the response of plants to the applied fertilizers. The aforementioned authors observed that SPAD and LAI indices in winter wheat could serve as predictors for plant growth and grain yield.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Szumiło and Rachoń [43] reported that delaying the sowing date primarily reduced the number of spikes per square meter. Sobko et al [44] demonstrated in their Jarecki and Czernicka [40] confirmed the usefulness of field measurements of plant parameters, such as SPAD and LAI, in assessing the effectiveness of fertilization of winter wheat and the response of plants to the applied fertilizers. The aforementioned authors observed that SPAD and LAI indices in winter wheat could serve as predictors for plant growth and grain yield.…”
Section: Resultsmentioning
confidence: 84%
“…Szumiło and Racho ń [43] reported that delaying the sowing date primarily reduced the number of spikes per square meter. Sobko et al [44] demonstrated in their study that different sowing dates did not affect the number of grains per spike but significantly modified TGW. The latter authors obtained the lowest TGW after sowing wheat on October 10 or 20.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The introduction of 90 kg ha -1 of phosphorus fertilizer at the beginning of flowering increased productivity and improved the quality of Onobrychis viciifolia herbage. Phosphorus supplementation improve the dry mass accumulation and the chemical compound of legumes [Comakli and Tas, 1996;Türk et al, 2007;Shalyuta and Kostitskaya, 2018;Sikora et al, 2020;Sobko et al, 2023] showed that fertilization with P increased the dry matter yield, the content of P, Ca, and Mg in the products, and the amino acid composition. The nutrient content is not necessarily the only criterion for assessing plant nutritional value [Thomson, 1982 Sainfoin responds well to the application of 60 kg ha -1 of nitrogen on frozen soil before the onset of vegetative growth, or they are mixed by cultivators to a depth of 10-12 cm.…”
Section: Introductionmentioning
confidence: 99%